Teacher Attitudes on Creativity - Luke Johnson (International Journal of Educational Spectrum, 2023)
Teacher attitudes affect student achievement, satisfaction, and self-worth. While accommodations and support networks have long been established for students with exceptional abilities (e.g. gifted-talented students and student athletes), creative students are largely ignored in curriculum and school support. Generally, teachers support creativity in principle, but creative students exhibit characteristics and behaviors largely deemed undesirable, although creative people and students can further studies regarding Csikszentmihalyi’s concepts of flow. The basic question of concern is this: What are teacher attitudes towards creativity and creative students? This literature review attempts to understand teacher attitudes, feelings, perspectives, or emotions regarding creativity, with a call for further research and study.